POSSIBILITIES OF ORGANIZING AND DEVELOPING CAMPSITES IN THE TERRITORY OF THE ZOMIN NATIONAL NATURE PARK (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article is devoted to the role of natural park of Zomin.